"The British Soldier is no Bolshevik": The British Army, Discipline, and the Demobilization Strikes of 1919. (13th December 2018) - Butler, William
Abstract: This article considers the breakdown in discipline in the British Army which occurred in Britain and on the Western Front during the process of demobilization at the end of the First World War. Many soldiers, retained in the army immediately after the Armistice, went on strike, and some formed elected committees, demanding their swifter return to civilian life. Their perception was that the existing demobilization system was unjust, and men were soon organized by those more politically conscious members of the armed forces who had enlisted for the duration of the war. At one stage in January 1919, over 50, 000 soldiers were out on strike, a fact that was of great concern to the British civilian and military authorities who miscalculated the risk posed by soldiers. Spurred on by many elements of the press, especially the Daily Mail and Daily Herald, who both fanned and dampened the flames of discontent, soldiers' discipline broke down, demonstrating that the patriotism which had for so long kept them in line could only extend so far. Though senior members of the government, principally Winston Churchill, and the military, especially Douglas Haig and Henry Wilson, were genuinely concerned that Bolshevism had 'infected' the army, or, at the very least, the army had been unionized, their fears were not realized. The article examines the government's strategy regarding demobilization, its efforts to assess the risk of politicization and manage the press, and its responses to these waves of strikes, arguing that, essentially, these soldiers were civilians first and simply wanted to return home, though, in the post-war political climate, government fears were very real.